Beneficial effect of moderate exercise in kidney of rat after chronic consumption of cola drinks - Cao, Gabriel Fernando (2016)
Aim: The purpose of this study was to investigate the effect of moderate intensity exercise on kidney in an animal model of high consumption of cola soft drinks. Methods: Forty-eight Wistar Kyoto rats (age: 16 weeks; weight: 350-400 g) were assigned to the following groups: WR (water runners) drank water and submitted to aerobic exercise; CR (cola runners) drank cola and submitted to aerobic exercise; WS (water sedentary) and CS (cola sedentary), not exercised groups. The aerobic exercise was performed for 5 days per week throughout the study (24 weeks) and the exercise intensity was gradually increased during the first 8 weeks until it reached 20 meters / minute for 30 minutes. Body weight, lipid profile, glycemia, plasma creatinine levels, atherogenic index of plasma (AIP) and systolic blood pressure (SBP) were determined. After 6 months all rats were sacrificed. A kidney histopathological score was obtained using a semiquantitative scale. Glomerular size and glomerulosclerosis were estimated by point-counting. The oxidative stress and proinflammatory status were explored by immunohistochemistry. A one way analysis of variance (ANOVA) with Tukey-Kramer post-hoc test or the Kruskal-Wallis test with Dunn's post-hoc test was used for statistics. A value of p < 0.05 was considered significant. Results: At 6 months, an increased consumption of cola soft drink was shown in CS and CR compared with water consumers (p<0.0001). Chronic cola consumption was associated with increased plasma triglycerides, AIP, heart rate, histopathological score, glomerulosclerosis, oxidative stress and pro-inflammatory status. On the other hand, moderate exercise prevented these findings. No difference was observed in the body weight, SBP, glycemia, cholesterol and plasma creatinine levels across experimental groups. Conclusions: This study warns about the consequences of chronic consumption of cola drinks on lipid metabolism, especially regarding renal health. Additionally, these findings emphasize the protective role of exercise training on renal damage.